2011
DOI: 10.1007/s13239-011-0062-6
|View full text |Cite
|
Sign up to set email alerts
|

Flow Visualization of the Penn State Pulsatile Pediatric Ventricular Assist Device Cannulae and Change in Outlet Valve Placement

Abstract: Due to the lack of long-term mechanical circulatory support options for children, Penn State is developing a pneumatically driven 12 cc pulsatile pediatric ventricular assist device (PVAD). The reduction in volume, however, necessary to accommodate pediatric patients leads to changes in the functional fluid mechanics. One area that has not been previously observed is the flow upstream and downstream of the inlet and outlet valves. In particular an area of blockage, that includes a large area of stagnant flow, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…17,18 Similarly, for others PVADs, the best angle was 15°. 13,19,20 So far, the fluid dynamics has indicated that the best angles for a bileaflet valve with two major orifices are 0°, 15°, and 30°.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 Similarly, for others PVADs, the best angle was 15°. 13,19,20 So far, the fluid dynamics has indicated that the best angles for a bileaflet valve with two major orifices are 0°, 15°, and 30°.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with tilting‐disc valves had shown that 45° (considering the major orifice of the valve facing the outside of the device) was the best choice for adult VADs 17,18 . Similarly, for others PVADs, the best angle was 15° 13,19,20 . So far, the fluid dynamics has indicated that the best angles for a bileaflet valve with two major orifices are 0°, 15°, and 30°.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation